The importance of integrons for development and propagation of resistance in Shigella: the case of Latin America - Barrantes Jiménez, Kenia (2016)
In Latin America, the disease burden of shigellosis is found to coexist with the rapid and rampant spread of resistance to commonly used antibiotics. The molecular basis of antibiotic resistance lies within genetic elements such as plasmids, transposons, integrons, genomic islands, etc., which are found in the bacterial genome. Integrons are known to acquire, exchange, and express genes within gene cassettes and it is hypothesized that they play a significant role in the transmission of multidrug resistance genes in several Gram-negative bacteria including Shigella. A few studies have described antibiotic resistance genes and integrons among multidrug resistant Shigella isolates found in Latin America. For example, in Brazil, Bolivia, Chile, Costa Rica and Peru, class 1 and class 2 integrons have been detected among multidrug resistant strains of Shigella; this phenomenon is more frequently observed in S. flexneri isolates that are resistant to trimethoprim, sulfamethoxazole, streptomycin, ampicillin, chloramphenicol, and tetracycline. The gene cassette sul2, which is frequently detected in Shigella strains resistant to the sulfonamides, suggests that the sulfonamide-resistant phenotype can be explained by the presence of the sul2 genes independent of the integron class detected. It is to be noted that sul3 was negative in all isolates analyzed in these studies. The high frequency of sulfonamide (as encoded by sul2) and trimethoprim resistance is likely to be a result of the recurrent use of trimethoprim sulfamethoxazole as a popular regimen for the treatment of shigellosis. The observed resistance profiles of Shigella strains confirm that ampicillin and trimethoprim-sulfamethoxazole are ineffective as therapeutic options. In-depth information regarding antibiotic resistance mechanism in this pathogen is needed in order to develop suitable intervention strategies. There is a pressing need for regional and local antimicrobial resistance profiling of Shigella to be included as a part of the public health strategy.